From the history of Ukrainian vertep (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The article is devoted to description of main stages of the history of Ukrainian nativity scene – from the end of sixteenth century to modern times. It is noted that performances were organized usually on Christmas and other religious holidays, that «live» nativity scene operates in parallel with the puppet theater for centuries, where the professional or amateur actors perform roles, that «live» nativity scene is very popular in our days.
Keywords: nativity scene; spiritual drama; sideshow; brave Zaporozhets; Muscovite